Changing Ethics Policies Without Scandal: State Responses to Published Reports and the Importance of Accurate Information. (2nd July 2016) - Rauh, William Jonathan
Abstract : This article details how states responded to the State Integrity Investigation—a large-scale study that sought to rank states based on their risk of corruption. Although some states responded with policy changes, the article demonstrates that responses were not due to how well the states performed compared to other states. Rather, their ranks on the survey magnified the effect of prior information on the state's ethics policies. Additionally, it goes on to show flaws in the ranking methods used in the State Integrity Investigation and demonstrates that these ranks likely created inconsistent responses from states with regard to changing ethics policies.